(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2018)
Forty years after the adoption of law 194/78 on voluntary termination of pregnancy, Italy still encounters difficulties in ensuring prompt access to abortion services. In particular, heated debates on conscientious objection are still ongoing. Given current discussions in other countries, the article suggests adopting a comparative perspective in order to renew the discussion and to address issues concerning, on the one hand, the extent to which a medical practitioner may refuse to participate in abortion procedures and, on the other hand, the necessity to guarantee full implementation of the law despite a limited number of doctors willing to perform abortions.